Natural Resources Management Based on Local Social Welfare in Nagari Sungai Antuan, Lima Puluh Kota District - Nefilinda, Nefilinda (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this study is to reveal and analyze the management of natural resources based on local wisdom on the welfare of the community in Nagari Sungai Antuan, Lima Puluh Kota District. This research uses qualitative methods. Primary data were obtained from interviews with informants (community) and key informants (Wali Nagari, Niniak Mamak and Clean Water Management). The location of the research is in Nagari Sungai Antuan, Lima Puluh Kota district. The results of the study: forest management system or ulayat land is principled ganggam bauntuak based on kinship system, although the ownership of forest or ulayat land based on tribe. In case of a dispute between the tribe then settled by Niniak Mamak among the disputing tribes. The value of custom which feels thick here like gotong royong and often held musyawarah. Some local wisdom of society in Nagari Sungai Antuan are: 1) Manage gambier, 2) Manage mixed garden, 3) Manage paddy field and 4) Manage water resources.